Coronavirus Disease (Covid-19) Associated Mucormycosis (CAM): Case Report and Systematic Review of Literature - Garg, Deepak; Muthu, Valliappan; Sehgal, Inderpaul Singh; Ramachandran, Raja; Kaur, Harsimran; Bhalla, Ashish; Puri, Goverdhan D.; Chakrabarti, Arunaloke; Agarwal, Ritesh (Mycopathologia (1975), 2021)
Severe coronavirus disease (COVID-19) is currently managed with systemic glucocorticoids. Opportunistic fungal infections are of concern in such patients. While COVID-19 associated pulmonary aspergillosis is increasingly recognized, mucormycosis is rare. We describe a case of probable pulmonary mucormycosis in a 55-year-old man with diabetes, end-stage kidney disease, and COVID-19. The index case was diagnosed with pulmonary mucormycosis 21 days following admission for severe COVID-19. He received 5 g of liposomal amphotericin B and was discharged after 54 days from the hospital. We also performed a systematic review of the literature and identified seven additional cases of COVID-19 associated mucormycosis (CAM). Of the eight cases included in our review, diabetes mellitus was the most common risk factor. Three subjects had no risk factor other than glucocorticoids for COVID-19. Mucormycosis usually developed 10–14 days after hospitalization. All except the index case died. In two subjects, CAM was diagnosed postmortem. Mucormycosis is an uncommon but serious infection that complicates the course of severe COVID-19. Subjects with diabetes mellitus and multiple risk factors may be at a higher risk for developing mucormycosis. Concurrent glucocorticoid therapy probably heightens the risk of mucormycosis. A high index of suspicion and aggressive management is required to improve outcomes.